An introduction to non-Abelian discrete symmetries for partical physicists (Springer Verlag, 2012)
The series Lecture Notes in Physics (LNP), founded in 1969, reports new develop-ments in physics research and teaching—quickly and informally, but with a high quality and the explicit aim to summarize and communicate current knowledge in an accessible way. Books published in this series are conceived as bridging mate-rial between advanced graduate textbooks and the forefront of research and to serve three purposes:• to be a compact and modern up-to-date source of reference on a well-defined; topic • to serve as an accessible introduction to the field to postgraduate students and nonspecialist researchers from related areas • to be a source of advanced teaching material for specialized seminars, courses and schools